State and prospects of development of tomato breeding in modern market conditions - I. V. Kozlova (Овощи России, 2021)
Relevance. To meet the needs of the population and commodity producers in the south of Russia in tomatoes, it is necessary to develop varieties and hybrids of various directions that have high productivity, increased fruit quality and resistance to fungal and bacterial diseases, that meet modern production technologies and market requirements, as well as have an acceptable price for seeds.Aim of study – creation of new maternal tomato lines with functional male sterility for open ground for various purposes (for fresh consumption, whole-fruit canning,), which will make it possible to create highly productive hybrids that meet the agro-climatic conditions of the south of Russia in the future.Materials and methods. The studies were carried out in a breeding film greenhouse and in field conditions on the territory of the experimental plot of FSBSI "Federal Scientific Rice Centre" of the central soil-climatic zone of Krasnodar region. The object of research were mid-ripening tomato varieties included in the competitive testing, sterile tomato lines, new F1 hybrids based on FMS, collection and breeding material. The types of crosses used in the work: analyzing, saturating, top-crosses. To speed up the process of developing new sterile tomato lines in winter, artificial climate chambers were used.Results. As a result of the research, promising new functionally sterile lines of tomato were identified, differing in the length of the vegetation period, weight, color, fruit shape, biochemical parameters, with a number of useful economically valuable traits.